Pakistan : Financial Sector Assessment Program-Technical Note-Condition of the Banking System. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Technical Note examines the condition of the banking system for Pakistan. The number of commercial banks and various nonbank financial institutions in the country grew rapidly in the early 1990s. The privatization of state-owned banks has been accompanied by the liberalization in the financial system and the openness to domestic and foreign competition. This technical note assesses the financial soundness indicators. It also contains the mission's recommendations aimed at preserving stability and soundness of the banking system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet